Analysis of the Application of Micro Steel Pipe Pile Technology in Emergency Maintenance of Ordinary National and Provincial Trunk Highway Subgrade - Wang, Xinchang (Journal of Theory and Practice of Management Science, 2023)
A provincial road in Guizhou Province experienced cracking and bursting of retaining walls, roadbed subsidence, and road surface cracking, with a rapid trend of disease development. After multiple on-site inspections, it was decided to implement emergency maintenance of the roadbed. For sudden disaster sections that affect traffic safety, emergency plans should be initiated and emergency maintenance and repair work should be carried out in a timely manner. The treatment plan adopts micro steel pipe piles to reinforce the roadbed, demolish and rebuild the original retaining wall, and finally restore the road surface, drainage, and traffic safety facilities.